STRATEGI PENINGKATAN PASRTISIPASI MASYARAKAT LOKAL DENGAN PENDEKATAN BERBASIS COMMUNITY BASED TOURISM DI DESA WISATA MUNGGU, KABUPATEN BADUNG, BALI - Muhammad Indra Prayoga; I Made Adikampana, Saptono Nugroho (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Munggu Tourism Village in Badung Regency, Bali, represents a paradox in rural tourism development: despite being recognized as a "developed" tourism village with the highest visitor volume in its region, the qualitative level of local community participation remains shallow and reactive. This study aims to analyze the root causes of this condition and formulate a strategic framework to transform the participation model from induced to authentic spontaneous participation. Using a qualitative case study approach, data were collected through in-depth interviews, non-participant observation, and document analysis. Data analysis was conducted using a conceptual framework integrating Tosun's (2006) participation typology, Community- Based Tourism (CBT) principles, and the Tri Hita Karana philosophy. The findings indicate that the dominant induced participation is not a reflection of the community's lack of will, but a logical response to a series of interconnected structural barriers: legal uncertainty over business land status, bureaucratic delays in disbursing development funds, and a fundamental mismatch between the village's unique cultural assets and the existing tourist market segment. As a solution, this study proposes a holistic framework focused on the four pillars of CBT: (1) strengthening engagement and ownership through customary-based land dispute resolution; (2) environmental preservation through community-based incentive programs; (3) cultural livelihood development through product diversification into experiential tourism; and (4) equitable economic benefit distribution through community investment schemes and transparent development funds. This framework offers a replicable model for fostering sustainable tourism genuinely rooted in community empowerment